Sous la croix gammée
Continued by: Fascisme (ZK 16071). - German ed.: Hakenkreuz über Deutschland (ZK 16067). - Eng. ed.: Germany under the swastika (ZK 53401). - Swedish ed.: Tyskland under hakkorset (ZK 53400). - Spanish ed.: Bajo la esvástica (ZK 53402).